2020
DOI: 10.1093/ehjacc/zuaa008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of major adverse cardiac events following non-cardiac surgery

Abstract: Aims Major adverse cardiac events (MACE) triggered by non-cardiac surgery are prognostically important perioperative complications. However, due to often asymptomatic presentation, the incidence and timing of postoperative MACE are incompletely understood. Methods and results We conducted a prospective observational study implementing a perioperative screening for postoperative MACE [cardiovascular death (CVD), acute heart fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
3
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 34 publications
0
49
3
13
Order By: Relevance
“…Early multicenter cohort studies reported in the past 2 decades have shown an incidence of MACE ranging from 1% to 7% in noncardiac surgeries comprising a large variety of surgeries and patients with widely different preoperative cardiac risks. [ 4 12 13 14 ] The incidence of 11.3% cardiac events that we report is, however, less than the 15.2% reported by Sazgary et al ,[ 5 ] wherein the focus was on noncardiac surgeries done in high-risk patients similar to our cohort; they found a high incidence of MACE in vascular surgeries, second only to thoracic surgeries. Their markedly higher incidence could be due to the older age group of patients in their cohort, median age of 73 years, inclusion of emergency surgeries with inadequate preoperative optimization, and an improved screening method for MACE.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Early multicenter cohort studies reported in the past 2 decades have shown an incidence of MACE ranging from 1% to 7% in noncardiac surgeries comprising a large variety of surgeries and patients with widely different preoperative cardiac risks. [ 4 12 13 14 ] The incidence of 11.3% cardiac events that we report is, however, less than the 15.2% reported by Sazgary et al ,[ 5 ] wherein the focus was on noncardiac surgeries done in high-risk patients similar to our cohort; they found a high incidence of MACE in vascular surgeries, second only to thoracic surgeries. Their markedly higher incidence could be due to the older age group of patients in their cohort, median age of 73 years, inclusion of emergency surgeries with inadequate preoperative optimization, and an improved screening method for MACE.…”
Section: Discussioncontrasting
confidence: 57%
“…[ 10 ] Hemodynamically relevant arrhythmias were defined as cardiac arrest, sustained ventricular tachycardia, atrial fibrillation with the need of treatment, and atrioventricular block III. [ 5 ] Cardiovascular death included death attributable to PMI, sudden cardiac arrest, acute heart failure, stroke, cardiovascular procedure, and pulmonary embolism. [ 11 ] Secondary outcome parameters such as duration of mechanical ventilation, need for tracheostomy, duration of ICU stay and hospital stay, the incidence of acute kidney injury and stroke, and in-hospital mortality were noted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 49 Little is known about cardiac complications following invasive dental interventions in women. Following non-cardiac surgery, limited evidence suggests that there are no sex differences in major adverse cardiac events 50 ; however, the literature is evolving and many issues remain to be firmly established, 51 , 52 including the effect of sex on patients’ risk. In general, women with cardiac disease experience greater morbidity and mortality compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also reported that Chinese patients who had any pre-existing MI or stroke were 2.87 times (Hazard ratio, HR = 2.872, 95% CI: 1.503–5.487) more likely to have a subsequent CVD event in 3 years [ 6 ]. In another study, for patients who received major surgical operations, peri-operative MI increased the risk of subsequent major adverse cardiac events (MACE) by 70% in the following year [ 7 ]. A study among hip fracture patients reported that patients with pre-existing heart failure had a higher one year post-operative heart failure exacerbation (HR = 3.00, 95% CI: 2.32–3.87) and one year mortality (HR = 2.11, 95% CI: 1.67–2.67) compared to those who did not have underlying or pre-existing heart conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%